2020
DOI: 10.1109/tcsii.2019.2952591
|View full text |Cite
|
Sign up to set email alerts
|

A 12.5 Gb/s 1.93 pJ/Bit Optical Receiver Exploiting Silicon Photonic Delay Lines for Clock Phases Generation Replacement

Abstract: This brief describes a high-speed optoelectronic receiver implemented in 65 nm CMOS technology. The receiver utilizes only two clock phases instead of the four conventionally used in a quarter-rate clocking system. This two-clock phase system is enabled by a passive silicon photonic split and delay structure that eliminates the need for a quadrature clock phase generator and all the associated buffers. Moreover, the outputs of the receiver are demultiplexed which further helps reducing power consumption in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The sensitivity of the proposed system is, theoretically, 3 dB below a full-bandwidth system operating at the same data rate due to the excess insertion loss of the delay lines. Moreover, as indicated by (17), the front end boosts the sensitivity of the electronic part of the receiver by 3.8 dB when the bandwidth is 0.35× data rate in comparison with a current amplifier-based receiver and by 3 dB in comparison with the integrating front-end receiver. As a result, the sensitivity of the proposed receiver is only 2.2 and 3 dB below these systems, respectively, considering the 6-dB optical losses.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The sensitivity of the proposed system is, theoretically, 3 dB below a full-bandwidth system operating at the same data rate due to the excess insertion loss of the delay lines. Moreover, as indicated by (17), the front end boosts the sensitivity of the electronic part of the receiver by 3.8 dB when the bandwidth is 0.35× data rate in comparison with a current amplifier-based receiver and by 3 dB in comparison with the integrating front-end receiver. As a result, the sensitivity of the proposed receiver is only 2.2 and 3 dB below these systems, respectively, considering the 6-dB optical losses.…”
Section: Discussionmentioning
confidence: 96%
“…From 15, a PD with high responsivity and small junction capacitance is desirable for optimal sensitivity. Moreover, the current is integrated over a full UI (T b ) in (16) or two full UIs (2T b ) in (17) and (18), as opposed to the 0.5 T b and 0.75 T b used in resettable receiver front ends and current-amplifierbased receivers, respectively. It can also be shown that v 01 is equal to v 11 − v 10 from the three v equations, (16)- (18).…”
Section: B Analysis Of the Integrationmentioning
confidence: 99%
See 3 more Smart Citations